2019
DOI: 10.7150/ijms.35936
|View full text |Cite
|
Sign up to set email alerts
|

Agonist of PPAR-γ Reduced Epithelial-Mesenchymal Transition in Eosinophilic Chronic Rhinosinusitis with Nasal Polyps via Inhibition of High Mobility Group Box1

Abstract: Epithelial-mesenchymal transition (EMT) has been reported to occur in eosinophilic chronic rhinosinusitis with nasal polyps (ECRSwNP). Among the cytokines that cause EMT, high mobility group box 1 (HMGB1) has been shown to give rise to EMT in airway epithelial cells. However, the mechanism of HMGB1-induced EMT in ECRSwNP is unknown. We explored the mechanism and possible inhibitor. Immunohistochemistry (IHC), immunofluorescence (IF), and western blot assay were used to detect the expression and location of HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…PPAR-γ exerted a negative feedback on SNA upregulated mesenchymal gene PPAR-γ was well known to suppress EMT [31][32][33][34] and inhibit metastases of HCC [35]. PPAR-γ can also affect transcription of mesenchymal genes known to be suppressed by SNA.…”
Section: Sna Directly Upregulated Transcription Of Fn and Lef In Tumomentioning
confidence: 99%
“…PPAR-γ exerted a negative feedback on SNA upregulated mesenchymal gene PPAR-γ was well known to suppress EMT [31][32][33][34] and inhibit metastases of HCC [35]. PPAR-γ can also affect transcription of mesenchymal genes known to be suppressed by SNA.…”
Section: Sna Directly Upregulated Transcription Of Fn and Lef In Tumomentioning
confidence: 99%
“…PPAR-γ belongs to a superfamily of nuclear hormone receptors and has the function of modulating lipid/lipoprotein metabolism, cell cycle progression, cellular proliferation, and differentiation after binding to ligand, and has been described to be involved in EMT in CRSwNP. It has been shown that the PPAR-γ agonist rosiglitazone (ROG) has an inhibitory effect on HMGB1 (high mobility group box 1), a pro-inflammatory DNA-binding nuclear protein, inducing the epithelial cells to become mesenchymal-like cells and supporting the pathogenesis of eosinophilic chronic rhinosinusitis with nasal polyps ECRSwNP [ 49 ]. The agonist ROG reverted the effect of rhHMGB1 on EMT in ECRSwNP cells as well as the endogenous expression of HMGB1 induced by the treatment with lipopolysaccharide (LPS).…”
Section: Intra-cellular Signaling Transduction Mechanisms Underlyimentioning
confidence: 99%
“…The agonist ROG reverted the effect of rhHMGB1 on EMT in ECRSwNP cells as well as the endogenous expression of HMGB1 induced by the treatment with lipopolysaccharide (LPS). ROG is able to restore the effects of HMGB1 activation up-regulating the expression of Zonula occludens-1 (ZO-1) and E-cadherin, and down-regulating the expression of N-cadherin and vimentin, biomarkers of MSCs [ 49 ].…”
Section: Intra-cellular Signaling Transduction Mechanisms Underlyimentioning
confidence: 99%
“…PPARγ signaling pathway is also involved in EMT in CRSwNP. It has been shown that Rosiglitazone (ROG), a PPAR-γ agonist, has a inhibitory effect on HMGB1 (High Mobility Group Box 1), a pro-inflammatory DNA-binding nuclear protein, inducing the epithelial cells to become mesenchymal-like cells and supporting the pathogenesis of eosinophilic chronic rhinosinusitis with nasal polyps ECRSwNP [42]. ROG reverted the effect of rhHMGB1 on EMT in ECRSwNP cells as well as the endogenous expression of HMGB1 induced by the treatment with the lipopolysaccharide (LPS).…”
Section: Pparγ Signaling Pathway Is Involved In Crswnpmentioning
confidence: 99%
“…ROG reverted the effect of rhHMGB1 on EMT in ECRSwNP cells as well as the endogenous expression of HMGB1 induced by the treatment with the lipopolysaccharide (LPS). ROG is able to restore the effects of HMGB1 activation up-regulating the expression of ZO-1 (Zonula occludens-1) and E-cadherin and down-regulating the expression of N-cadherin and vimentin [42].…”
Section: Pparγ Signaling Pathway Is Involved In Crswnpmentioning
confidence: 99%